Respostas de clones de Eucalyptus grandis e E. grandis x E. urophylla à supressão de boro - Leite, Susi Meire Maximino; Marino, Celso Luis [UNESP]; Bonine, César Augusto Valencise (My University, 2010)
The present work had as objective the study of clones of Eucalyptus grandis and E. grandis × E. urophylla under boron suppression on growth in height and diameter, development of symptoms of deficiency, boron content in leaf and polyols production. Plants were cultivated in pots with quartz in a greenhouse using two levels of boron per solution (0 and 0.5 mg L-1 of B). The 32 treatments followed a factorial scheme: 16 × 2 -16 clones and two doses of boron in a randomized block experimental design, with fve repetitions, totaling 160 plots. Plants were evaluated weekly for deficiency symptoms and monthly for height, stem diameter and leaf content of boron in different plant parts. The content of polyols was measured in two occasions: at 162 days and 192 days after starting the experiment. Decrease of growth and quick development of deficiency symptoms 40 days after boron suppression were observed, as well as a decrease of polyols synthesis. Foliar analysis, with boron supplement, resulted in the presence of mannitol and sorbitol in high enough concentration so that the evaluated plants could be considered rich in those polyols. Under boron suppression, boron levels in different portions of branches and stems of plants, as well as the presence of mannitol and sorbitol, indicated a conditional mobility of boron in Eucalyptus.
Response of Eucalyptus grandis and E. grandis x E. urophylla clones to boron suppression
Keywords: Boron mobility; Carbohydrate synthesis; Plant mineral nutrition; Polyols; Boron content; Clones of Eucalyptus; Eucalyptus grandis; Experimental design; Mineral nutrition; Stem diameter; Alcohols; Boron; Carbohydrates; Nutrition; Oxide minerals; Quartz; Silicate minerals; Borate minerals